FUNGSI PEMERINTAH DAERAH KABUPATEN ROKAN HILIR DALAM MENGATASI KELANGKAAN LIQUEFIED PETROLEUM GAS (LPG) 3 KG TAHUN 2013 - Adri Wijaya; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aimed to determine and analyze the functions of local government district in the downstream rokan overcome the scarcity of LPG 3 kg in 2013. in Law No. 22 Year 2001 on Oil and Gas that LPG is an abbreviation of Liquefied Petroleum Gas, which means liquefied gas at a certain pressure derived from petroleum that has been fractionated. So the main source of producing LPG actually petroleum, natural gas instead. The research behind this is to see the number of people is increasing from year to year, causing greater levels of consumer needs and quotas khusunnya LPG LPG 3 kg was not able to meet the needs of society as a consumer.This study included into the qualitative research study using in-depth interview data collection techniques to several respondents (key informants) that have been assigned or puposive techniques .... the researchers selected a sample of informants criteria that truly understands the expected goal of researchers in research This as well as having an important position in the agency concerned.These results indicate that efforts by the local governments, especially the Department of Industry and Trade Rokan Hilir not perform its function optimally. Indicated by the scarcity of LPG 3 kg which occurred in Rokan downstream of this, due to the number of mafia / elements that playing field and there are many bases and retailers who do not comply with the rules set by the department of trade and industry. By selling price does not match the Rokan Hilir Regency Decree No. 291 of 2012 on the highest retail price (HET). In addition, there are several factors that led to the scarcity of LPG 3 kg of factors cause is the first ever increasing population which does not comply with the quota. Second, the movement of LPG LPG Gas 12 kg to 3 kg of LPG. Third, keberaaan SPBE as a supply point has not functioned optimally. Fourth, a very high demand by msayarakat as consumers.Key Words: Effort, The Functions Of Local Government, Energy Conservation